2013
DOI: 10.3389/fnagi.2013.00089
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory in amnestic-mild cognitive impairment: insights from event-related potentials

Abstract: Episodic memory loss is the hallmark cognitive dysfunction associated with Alzheimer’s disease (AD). Amnestic mild cognitive impairment (a-MCI) frequently represents a transitional stage between normal aging and early AD. A better understanding of the qualitative features of memory loss in a-MCI may have important implications for predicting those most likely to harbor AD-related pathology and for disease monitoring. Dual process models of memory argue that recognition memory is subserved by the dissociable pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 102 publications
1
14
0
6
Order By: Relevance
“…Otherwise, LPP retrieval-related activity has been associated with processes of familiarity and recollection (dual process model of recognition) [66] both of which contribute to performance on change detection tasks. Consistent with our results, a recent ERP study [67] showed that amnestic MCI patients present an attenuation of LPP waveforms during the performance of a recognition memory task when they retrieved memories based on recollection and familiarity processes. Thus, this evidence suggests that in MCI patients, reduced amplitude of LPP in the shape-color binding condition may involve retrieval affectation of recollection and familiaritybased memories, either because fewer items are retrieved, and/or fewer entire itemconfigurations have been successful retrieved.…”
supporting
confidence: 92%
“…Otherwise, LPP retrieval-related activity has been associated with processes of familiarity and recollection (dual process model of recognition) [66] both of which contribute to performance on change detection tasks. Consistent with our results, a recent ERP study [67] showed that amnestic MCI patients present an attenuation of LPP waveforms during the performance of a recognition memory task when they retrieved memories based on recollection and familiarity processes. Thus, this evidence suggests that in MCI patients, reduced amplitude of LPP in the shape-color binding condition may involve retrieval affectation of recollection and familiaritybased memories, either because fewer items are retrieved, and/or fewer entire itemconfigurations have been successful retrieved.…”
supporting
confidence: 92%
“…The present findings of perirhinal hypometabolism in APO-E4 carriers, correlated with performance on a memory task assessing context-free memory, also raise the question as to whether these subjects are at a preclinical stage of AD. However, more challenging neuropsychological tasks are more likely to reveal deficits and should ideally assess the function of the perirhinal cortex, such as familiarity-based recognition memory tasks that are thought to contribute to the preclinical diagnosis of AD [69,70] and tasks assessing visual short-term memory binding that is altered in asymptomatic mutation carriers in familial AD [71].…”
Section: Relationship Between Metabolic Changes and Cognitive Functionmentioning
confidence: 99%
“…Comme nous allons le voir, ces études ont mené à des résultats contradictoires, spécifiquement concernant l'intégrité de la familiarité dans ces populations. [16][17][18][19], le rappel de détails avec un degré élevé de certitude [20][21][22], la récupération contrôlée de détails spécifiques [16,[23][24][25][26], l'effet de référence à soi 3 [27] ou le sentiment subjectif de remémoration consciente et d'auto-référence généré par la réactivation de l'épisode [28][29][30][31][32][33]. Ce déficit massif de la recollection a été associé à une dysfonction et une atrophie de différentes régions du réseau cérébral générique de recollection [11], notamment de l'hippocampe [34,35], du cortex cingulaire postérieur et du cortex préfrontal dorsomédian [29,36] Un autre facteur lié à la méthodologie qui pourrait moduler l'impact de la maladie d'Alzheimer sur les formes de reconnaissance serait la nature du matériel utilisé, à savoir verbal ou non-verbal [13,38].…”
Section: Recollection Et Familiaritéunclassified
“…Ce déficit massif de la recollection a été associé à une dysfonction et une atrophie de différentes régions du réseau cérébral générique de recollection [11], notamment de l'hippocampe [34,35], du cortex cingulaire postérieur et du cortex préfrontal dorsomédian [29,36] Un autre facteur lié à la méthodologie qui pourrait moduler l'impact de la maladie d'Alzheimer sur les formes de reconnaissance serait la nature du matériel utilisé, à savoir verbal ou non-verbal [13,38]. A première vue, la majorité des études ayant montré une atteinte de la familiarité chez des patients souffrant d'une maladie d'Alzheimer ou d'un trouble cognitif léger ont utilisé des mots comme matériel [16,18,20,23,25,31,40].…”
Section: Recollection Et Familiaritéunclassified